INTRODUCTION TO CULTURAL STUDIES: A CONCEPTUAL AND EPISTEMOLOGICAL ANALYSIS - Machado dos Santos, Adelcio; Antonio Córdova Ransolin, Marco (Revista Gênero e Interdisciplinaridade, 2025)
This article presents a critical introduction to Cultural Studies, highlighting its conceptual and epistemological foundations. It begins by addressing the emergence of the field in the context of the Birmingham School, emphasizing its interdisciplinary nature and its commitment to analyzing cultural practices in relation to power, ideology, and identity. Central concepts such as culture, representation, hegemony, identity, and resistance, which underpin the critical perspective of Cultural Studies, are discussed. In addition, the article highlights the importance of the situated epistemological stance, which recognizes knowledge as constructed and imbued with power relations. The reception of Cultural Studies in Brazil is also examined, highlighting the articulation with local issues such as race, gender, class, and coloniality, which broadens the understanding of cultural dynamics in peripheral contexts. Finally, the relevance of Cultural Studies as a theoretical-methodological field for understanding and intervening in complex contemporary social relations is reaffirmed, strengthening practices of resistance and promotion of cultural diversity. This work contributes to the reflection on culture as a strategic field of symbolic dispute and to the strengthening of a critical, plural, and transformative science.